Kebijakan dan Pembangunan Sistem Ekonomi Pada Masa Rasulullah - Erika Safitri (Journal of Islamic Economic Studies, 2025)
Islamic economics has been a fundamental cornerstone of Muslim society since the time of the Prophet Muhammad. This research examines the Islamic economic system implemented by the Prophet, focusing on the principles of trade, fiscal policy, and economic development in Medina. This study uses a descriptive qualitative method with a literature study approach to describe the Prophet's economic policies systematically and analytically. The results show that the Prophet implemented fair, transparent, and sharia-based trading principles, and built an inclusive economic system through fiscal policies such as zakat, jizyah, and khums. In addition, monetary policy at that time prioritized financial stability without usury practices. These efforts contributed to the welfare of society and created an equitable and sustainable economic system. This study provides insight into how Islamic economic principles can be applied in the context of modern economics.